Community protection of the environment within the framework of UEMOA : challenges, scope and prospects - (:unkn) unknown (My University, 2019)
The West African Economic and Monetary Union (UEMOA), established in 1994, is one of the youngest economic integration organizations in West Africa. Set up at a time when all the lights on the sustainable management of natural resources were already on, it has however not explicitly enshrined the preservation of the environment in its Constitutive Treaty.UEMOA’s secondary law, which tends to fill in the gaps in its primary law, is unfortunately held hostage by complex and lengthy procedures. Thus, most of the legal instruments being developed remain at the stage of unfinished drafts. To rise to the rank of modern institutions committed to reconciling economy and ecology, a difficult but necessary undertaking, UEMOA should revise its primary law to include the preservation of the environment and sustainable development as one of its essential objectives. It should also speed up the final adoption of its many draft legal texts on the protection of the environment within the Union.
Keywords: African Research